Away from "unified nostalgia": conceptual differences of personal and historical nostalgia appeals in advertising - Marchegiani, Chris; Phau, Ian (Routledge Taylor and Francis Group, 2010)
Studies suggest that nostalgia can be split into two distinct forms; Personal and Historical nostalgia. This research explores these varieties of nostalgic appeal and, based on literature, proposes differing effects these variations may have on the important consumer behaviour responses of cognition, emotions, attitudes, and purchase intentions. A review of the literature suggests that significant differences will exist dependent on the type of nostalgic appeal being used. The call for scales to test these appeals independently of one another is also made. Finally, this evidence suggests that treatment of nostalgia as a 'unified' concept may be inaccurate in predicting true consumer responses and future studies should treat the two types as separate appeals if rigor is to be suggested.